Peranan Keuangan Mikro Syariah dalam Pemberdayaan UMKM di Gunung Kidul, Yogyakarta - Ikhcan Dwi Cahyono; Darmawan (CV. ALIM'SPUBLISHING, 2024)
This study aims to investigate the role of Islamic microfinance in empowering and improving the performance of Micro, Small, and Medium Enterprises (MSMEs) in Gunung Kidul, Yogyakarta. Islamic microfinance has become a major focus in efforts to support inclusive and sustainable economic growth, especially in the context of MSMEs in Indonesia. The research framework includes independent variables in the form of Islamic microfinance, mediating variables in the form of MSME empowerment, dependent variables in the form of MSME performance, and moderating variables involving external factors. The research method used is a cross-sectional survey with primary data collection through questionnaires. Data analysis was carried out using multiple regression techniques to test the relationship between variables and the moderating effect. The results of the study are expected to provide a deeper understanding of the impact of Islamic microfinance on MSME empowerment and performance, as well as its implications for the development of policies and business practices at the local level. The findings of this study are expected to provide a significant contribution to efforts to increase financial inclusion and sustainable economic growth in the Gunung Kidul area, Yogyakarta, and become a reference for further research in this field.